Integration of Hydrogen-Deuterium Exchange Mass Spectrometry with Molecular Dynamics Simulations and Ensemble Reweighting Enables High Resolution Protein-Ligand Modeling - Kihn, Kyle C; Purdy, Olivia; Lowe, Vincent; Slachtova, Lenka; Smith, Ally K; Shapiro, Paul; Deredge, Daniel J (Journal of the American Society for Mass Spectrometry, 2024)
Hydrogen-Deuterium exchange mass spectrometry's (HDX-MS) utility in identifying and characterizing protein-small molecule interaction sites has been established. The regions that are seen to be protected from exchange upon ligand binding indicate regions that may be interacting with the ligand, giving a qualitative understanding of the ligand binding pocket. However, quantitatively deriving an accurate high-resolution structure of the protein-ligand complex from the HDX-MS data remains a challenge, often limiting its use in applications such as small molecule drug design. Recent efforts have focused on the development of methods to quantitatively model Hydrogen-Deuterium exchange (HDX) data from computationally modeled structures to garner atomic level insights from peptide-level resolution HDX-MS. One such method, HDX ensemble reweighting (HDXer), employs maximum entropy reweighting of simulated HDX data to experimental HDX-MS to model structural ensembles. In this study, we implement and validate a workflow which quantitatively leverages HDX-MS data to accurately model protein-small molecule ligand interactions. To that end, we employ a strategy combining computational protein-ligand docking, molecular dynamics simulations, HDXer, and dimensional reduction and clustering approaches to extract high-resolution drug binding poses that most accurately conform with HDX-MS data. We apply this workflow to model the interaction of ERK2 and FosA with small molecule compounds and inhibitors they are known to bind. In five out of six of the protein-ligand pairs tested, the HDX derived protein-ligand complexes result in a ligand root-mean-square deviation (RMSD) within 2.5 Å of the known crystal structure ligand.
Keywords: HDXer; Ligands; ERK2; Protein Conformation; Hydrogen Deuterium Exchange-Mass Spectrometry; HDX-MS; Protein−Ligand Modeling; proteiny; ligandy; vazba proteinů; vazebná místa; simulace molekulární dynamiky; Hydrogen−Deuterium Exchange; Molecular Dynamics Simulation; FosAKP; Molecular Dynamics Simulations; Maximum Entropy Reweighting; simulace molekulového dockingu; Protein Binding; Proteins; Protein−Small Molecule Interactions; vodík/deuteriová výměna a hmotnostní spektrometrie; Computational Docking; Binding Sites; konformace proteinů; Molecular Docking Simulation; Structure Based Drug Design